2020
DOI: 10.1186/s12931-020-1278-5
|View full text |Cite
|
Sign up to set email alerts
|

Reduced airway levels of fatty-acid binding protein 4 in COPD: relationship with airway infection and disease severity

Abstract: Background: For still unclear reasons, chronic airway infection often occurs in patients with Chronic Obstructive Pulmonary Disease (COPD), particularly in those with more severe airflow limitation. Fatty-acid binding protein 4 (FABP4) is an adipokine involved in the innate immune response against infection produced by alveolar macrophages (Mɸ). We hypothesized that airway levels of FABP4 may be altered in COPD patients with chronic airway infection. Methods: In this prospective and controlled study we: (1) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…Lack of IFNs can lead to excessive viral production 33 and cause life-threating COVID-19 in patients deficient in functional IFNs due to, for example, the occurrence of loss-of-function mutations in genes governing IFN-mediated immunity 32 or auto-antibodies against IFNs 31 . Further, FABP4+ alveolar macrophages were observed to be largely absent in patients with severe COVID-19, but were a predominant macrophage in patients with mild disease 50 , indicating the major role of FABP4+ alveolar macrophages in controlling infection as also shown previously for patients with chronic obstructive pulmonary disease (COPD) 51 . We assume a constant supply of macrophages in the lungs and MPS in our model, but a deleterious effect of infection on these immune cells cannot be ruled out, and further experimental evidence is necessary to model the cell population kinetics appropriately 52 .…”
Section: Resultssupporting
confidence: 75%
“…Lack of IFNs can lead to excessive viral production 33 and cause life-threating COVID-19 in patients deficient in functional IFNs due to, for example, the occurrence of loss-of-function mutations in genes governing IFN-mediated immunity 32 or auto-antibodies against IFNs 31 . Further, FABP4+ alveolar macrophages were observed to be largely absent in patients with severe COVID-19, but were a predominant macrophage in patients with mild disease 50 , indicating the major role of FABP4+ alveolar macrophages in controlling infection as also shown previously for patients with chronic obstructive pulmonary disease (COPD) 51 . We assume a constant supply of macrophages in the lungs and MPS in our model, but a deleterious effect of infection on these immune cells cannot be ruled out, and further experimental evidence is necessary to model the cell population kinetics appropriately 52 .…”
Section: Resultssupporting
confidence: 75%
“…Lack of IFNs can lead to excessive viral production and cause life-threating COVID-19 in patients deficient in functional IFNs due to, for example, the occurrence of loss-of-function mutations in genes governing IFN-mediated immunity or autoantibodies against IFNs . Further, FABP4+ alveolar macrophages were observed to be largely absent in patients with severe COVID-19 but were the predominant macrophage in patients with mild disease, indicating the major role of FABP4+ alveolar macrophages in controlling infection as also shown previously for patients with chronic obstructive pulmonary disease (COPD) . We assume a constant supply of macrophages in the lungs and MPS in our model, but a deleterious effect of infection on these immune cells cannot be ruled out, and further experimental evidence is necessary to model the macrophage population kinetics more appropriately .…”
Section: Resultssupporting
confidence: 68%
“…32 Further, FABP4+ alveolar macrophages were observed to be largely absent in patients with severe COVID-19 but were the predominant macrophage in patients with mild disease, 57 indicating the major role of FABP4+ alveolar macrophages in controlling infection as also shown previously for patients with chronic obstructive pulmonary disease (COPD). 58 We assume a constant supply of macrophages in the lungs and MPS in our model, but a deleterious effect of infection on these immune cells cannot be ruled out, and further experimental evidence is necessary to model the macrophage population kinetics more appropriately. 59 Further, the model reveals that the effect of adaptive immunity (antibodies and CD8* cells) is not significant in controlling infection, but it does not necessarily rule out the therapeutic potential of exogenously administered antibodies or novel cell-based therapies (e.g., T cell therapy).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…FABP4 levels also positively correlated with adiponectin and tumor necrosis factor α in COPD patients [ 13 ]. On the contrary, another study has revealed that airway FABP4 levels are reduced in COPD patients [ 14 ]. Although the above studies reported the controversial effect of FABP4 on COPD, they all suggested the important role of FABP4 in COPD pathogenesis.…”
Section: Introductionmentioning
confidence: 99%